Job Displacement, Unemployment Benefits and Domestic Violence - Sonia R. Bhalotra; Diogo Britto; Paolo Pinotti; Breno Sampaio (Institute of Labor Economics (IZA), 2021)
We estimate impacts of male job loss, female job loss, and male unemployment benefits on domestic violence in Brazil. We merge employer-employee and social welfare registers with administrative data on domestic violence cases brought to criminal courts, use of public shelters by victims and mandatory notifications of domestic violence by health providers. Leveraging mass layoffs for identification, we find that both male and female job loss, independently, lead to large and pervasive increases in domestic violence. Exploiting a discontinuity in unemployment insurance eligibility, we find that eligible men are not less likely to commit domestic violence while benefits are being paid, and more likely to commit it once benefits expire. Our findings are consistent with job loss increasing domestic violence on account of a negative income shock and an increase in exposure of victims to perpetrators, with unemployment benefits partially offsetting the income shock while reinforcing the exposure shock.
Keywords: J16; J08; 330; domestic violence; unemployment; mass layoffs; unemployment insurance; income shock; exposure; Brazil